Tropospheric pyruvate changes in the remote area of northwestern China - 李心清 秦大河 江伟 蒋倩 (Acta geochimica, 2005)
Pyruvate is a light carboxylate in the troposphere and can act as potential cloud condensation nuclei. Due to its low concentrations, however, little work has been done on the species in precipitation.Past 43-year record of pyruvate was recovered from an ice core of Glacier 1 at 43°06＇N and 86°49＇E in the remote East Tianshan, northwestern China. It was revealed that pyruvate varied over a relatively large range with some below the detection limit, while part of it is so high as to be up to 70 ng · g^-1. With an average concentration of 4.1 ± 8.1 ng · g^-1 （mean ± 1σ, N =543） , pyruvate is a minor species in comparison with other carboxylates. It is also low as compared with its precipitation in other parts of the world, suggesting a difference in its major source flux. The record revealed high pyruvate concentrations in the late halves of the 1950s and 1980s, but low in the late 1950s, late 1970s, and middle 1990s. The variation trend in the past 43 years is closely correlated with that of acetate, a major carboxylate from anthropogenic pollution to the atmosphere, indicating that tropospheric pyruvate in the remote area of northwestern China is probably a by-product in acetate formation.